Biocatalytic synthesis of 3, 4, 5, 3′, 5′-pentahydroxy-trans-stilbene from piceatannol by two-component flavin-dependent monooxygenase HpaBC. Issue 1 (2nd January 2016) - Furuya, Toshiki; Sai, Masahiko; Kino, Kuniki
Abstract: HpaBC monooxygenase was previously reported to hydroxylate resveratrol to piceatannol. In this article, we report a novel catalytic activity of HpaBC for the synthesis of a pentahydroxylated stilbene. When Escherichia coli cells expressing HpaBC were incubated with resveratrol, the resulting piceatannol was further converted to a new product. This product was identified by mass spectrometry and NMR spectroscopy as a 5-hydroxylated piceatannol, 3, 4, 5, 3′, 5′-pentahydroxy- trans -stilbene (PHS), which is a reportedly valuable biologically active stilbene derivative. We attempted to produce PHS from piceatannol on a flask scale. After examining the effects of detergents and buffers on PHS production, E. coli cells expressing HpaBC efficiently hydroxylated piceatannol to PHS in a reaction mixture containing 1.5% (v/v) Tween 80 and 100 mM 3-morpholinopropanesulfonic acid-NaOH buffer at pH 7.5. Under the optimized conditions, the whole cells regioselectively hydroxylated piceatannol, and the production of PHS reached 6.9 mM (1.8 g L −1 ) in 48 h. Graphical abstract: : HpaBC regioselectively hydroxylates piceatannol to 3, 4, 5, 3′, 5′-pentahydroxy- trans -stilbene, a valuable biologically active stilbene derivative.